2017
DOI: 10.22462/1.2.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive hyperbaric oxygen treatment for idiopathic sudden sensorineural hearing loss

Abstract: Introduction: This study aims to evaluate the hearing gain efficacy from adjunctive hyperbaric oxygen (HBO2) treatment in patients with idiopathic sudden sensorineural hearing loss (ISSHL). Materials and Methods: A retrospective analysis of chart reviews was performed on patients with ISSHL between January 2013 through December 2015. All patients were referred to us from our ENT Department for adjunctive hyperbaric oxygen treatment. The results were assessed through pure-tone audiometry (PTA) data change (hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Some studies reported that HBO therapy is better for those with initial severe hearing loss [ 2 , 7 , 8 , 10 ]. Some studies indicate that patients with moderate ISSHL are improved by HBO therapy along with oral steroids, but HBO therapy is ineffective for patients with severe and profound hearing losses [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies reported that HBO therapy is better for those with initial severe hearing loss [ 2 , 7 , 8 , 10 ]. Some studies indicate that patients with moderate ISSHL are improved by HBO therapy along with oral steroids, but HBO therapy is ineffective for patients with severe and profound hearing losses [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cases where patients were unable to equalize their middle ear pressures, they were referred to our ENT department to receive a procedure of tympanic membrane puncture. With appropriate education and evaluation, only 30% of patients experienced pain at the eardrum during the HBO pressurizing step [ 8 ]. When such pain occurred, pressurizing speed was reduced, and time allowed for patients to adjust to pressure changes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, adequate assessment of the patient’s systemic status and past medical history is required prior to treatment, and the application of HBOT in diseases should be careful ( Table 1 ). 12 20 23 25 26 27 28 29 30 31 32 33 34 35 36 …”
Section: H Yperbaric O Xygenmentioning
confidence: 99%